Single locus microsatellite development for the Malaysian giant freshwater prawns, Macrobrachium rosenbergii - Bhassu, Subha (Universiti Putra Malaysia Press, 2005)
Prawns of the genus Macrobrachium Bate, 1868 (Crustacea: Palaemonidae) are a highly diverse group of decopod crustaceans found in circumtropical marine-, estuarine- and freshwaters. At present, wild stocks have been used to cultivate commercial cultures in many areas in Malaysia. Such repeated harvesting from wild stocks, however, will eventually lead to extinction and loss of genetic diversity. Therefore, it is important to know the genetic make up of these wild stocks in order to manage the populations for conservation and breeding purposes. In the present study, a novel method known as Random Amplified Microsatellites (RAMS) was used to develop single locus microsatellite markers. A total of 13 microsatellite regions were detected. The findings of this study showed a successful detection of the microsatellite sequences in M. rosenbergii using RAMS. This study will be continued to identify more clones that contain microsatellite sequences and to design the forward and reverse primers for each microsatelite region. M. rosenbergii sequences were homologous with Danio rerio (Zebra fish) and Perna viridis (green lipped mussel).